MANUSIA SEJATI DALAM FALSAFAH MBAH MARIDJAN DAN ABDUL KARIM AL-JILLI (Studi Konsepsi Manunggaling Kawula Gusti dan Insan Kamil) - Baharuddin, M (Analisis: Jurnal Studi Keislaman, 2013)
The  theory  of  spiritual  journey  between  Mbah  Maridjan  and Abdul Karim al-Jilli departed from the same starting point, which is a question of how human beings to be perfect? This paper up- raise the figure and ideas of Mbah Maridjan that  appears in the middle of situation  about an identity crisis and existential  crises, which tend to be materialists. Through a comparative study based on the  philosophy,  the  authors  found that  Mbah Maridjan,  the Javanese and Islamic wisdom, was capable of providing answers that  humans can be perfect if they have the will to continue  to find identity  though exploring the spiritual sense (sabawa rasa) that  in the  terminology  of Abdul-Karim  al Jilli-called  spiritual potential  (ru>h}iyyah-rabba>ninyyah), and constancy against human desires. Therefore, the final goal  that a man will go is unity with the Almighty God (Manunggaling Kawula Gusti). These level can only be achieved by the perfect man (Insa>n Ka>mil).